Bimbingan Konseling Islam Melalui Teknik Self Management untuk Meningkatkan Pemanfaatan Waktu Luang pada Remaja Putus Sekolah - Rahayu, Citra Repsi Tri; Kusnadi, Kusnadi; Rasmanah, Manah (Scidacplus, 2023)
This research aims to determine Islamic counseling guidance through self-management techniques in increasing the use of free time among out-of-school teenagers (R clients) in Daya Makmur Village, Muara Padang District, Banyuasin Regency. The main subject in this research is client